Mockery Phenomenon of Putin's Satire Depicted on the Russian and Ukrainian Memes : Fenomena Ejekan Sindiran Terhadap Putin Pada Meme Russia dan Ukraina - Salsa Amalia (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This paper observed the Russian and Ukrainian Memes as primarily focused on Putin’s humiliation-related memes on Twitter. This research explores how visual and verbal elements are arranged as multimodal properties to assess the use of contempt of the resentment applied O’Halloran (2008) Systemic Functional Multimodal Discourse Analysis and Generic Structure Potential (1989) proposed by Hasan. The study aims to reveal the concept of mockery portrayed in Russian and Ukrainian memes to show the connection between the visual and verbal elements. The data comprehend 15 Internet memes from Twitter, gathered on June 4, 2023, and were examined with a descriptive qualitative method because the data collection was conducted using documentation technique. The study determined that most of the verbal and visual resources depicted Putin’s satire identified from attitude concepts which show the negative judgment categories (Martin and White, 2005). In addition, the concept of mockery is not just abusive humor, but it also carries social criticism in sarcastic contexts.